Anestesia intravenosa total com cetamina-propofol ou cetamina-xilazina-egg em infusão contínua em asininos pré-medicados com xilazina - COELHO, Cássia Maria Molinaro (2009)
The dissociative anesthesia was receiving more attention as the inhalation anesthesia based in cardiorespiratory and economic results in horses. However, there are few studies in donkeys (Equus asinus). The aim of this research was evaluate and compare the cardiorespiratory, metabolic and electrocardiographic effects of ketamine-propofol (KP) and ketamine-xilazine-EGG (GKX) total intravenous anesthesia in donkeys. Eight healthy adult donkeys were anesthetized twice with seven days interval between protocols. In both protocols, the animals were premedicated with 1.0 mg/kg of xylazine. The protocol KP was induced with 1.5 mg/kg of ketamine and a loading dose of propofol (0.5 mg/kg). The animals were maintained in constant rate infusion of ketamine (0.05 mg/kg/min) and propofol (0.15 mg/kg/min) during one hour. In GKX protocol, the animals were induced with diazepam (0.05 mg/kg) and ketamine (2.2 mg/kg). So, the animals were maintained in constant rate infusion (2 ml/kg/h) of a solution prepared with an association of 5% guaifenesin (100 mg/kg), ketamine (2.0 mg/ml) and xylazine (0.5 mg/ml). The quality of induction and recovery were assessed using scores (1-good; 2-regular; 3-poor) and measured cardiorespiratory, metabolic and electrocardiographic parameters before, during and after the anesthetic procedure. The results showed that the ketamine-propofol and ketamine-xylazine-EGG associations were satisfactory to anesthetized the donkeys, whereas seven anesthetic inductions were classified as good (score 1) in both protocols. The heart rate was statistic different between protocols since 15M moment. The mean arterial pressure decreased during the procedure in KP and GKX. There were no statistic differences between protocols in PaO2, PaCO2, LACv e LACa. The arterial glucose showed higher elevation in GKX and statistic difference at recovery. There were no statistic differences regarding CK and AST serum values. Concerning the electrocardiographic assessment, the protocols did not result in abnormalities on the length and amplitude of waves and complexes that could compromise the cardiac dynamics. In conclusion, propofol-ketamine and ketamine-xylazine-EGG associations can be successfully employed in asinines for the accomplishment of procedures without painful stimuli. The cardiorespiratory, metabolic and electrocardiographic changes observed in the present study were not sufficient to cause systemic distress in healthy animals